2017
DOI: 10.3847/1538-4357/aa97d7
|View full text |Cite
|
Sign up to set email alerts
|

The Acceleration of High-energy Protons at Coronal Shocks: The Effect of Large-scale Streamer-like Magnetic Field Structures

Abstract: Recent observations have shown that coronal shocks driven by coronal mass ejections can develop and accelerate particles within several solar radii in large solar energetic particle (SEP) events. Motivated by this, we present an SEP acceleration study that including the process in which a fast shock propagates through a streamer-like magnetic field with both closed and open field lines in the low corona region. The acceleration of protons is modeled by numerically solving the Parker transport equation with spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 82 publications
2
55
0
Order By: Relevance
“…Such shocks can efficiently accelerate both the interacting protons producing the pion decay γ-ray emissions at the Sun and the interplanetary protons responsible for the prompt component of the GLE at the Earth. Several relevant acceleration models were considered by Kocharov et al (2011Kocharov et al ( , 2012, Kong et al (2017), and Kouloumvakos et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such shocks can efficiently accelerate both the interacting protons producing the pion decay γ-ray emissions at the Sun and the interplanetary protons responsible for the prompt component of the GLE at the Earth. Several relevant acceleration models were considered by Kocharov et al (2011Kocharov et al ( , 2012, Kong et al (2017), and Kouloumvakos et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting correlations are not statistically significant, and an apparent relation is difficult to establish from Figure 9. Recent studies have shown that for a realistic coronal structure the seed particles gain energy gradually by interacting with a rapidly varying shock geometry (e.g., Sandroos & Vainio 2009;Kong et al 2017). A proper evaluation of the role of shock geometry on the acceleration process requires a more refined analysis that folds in time dependency.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…They demonstrated that the familiar planar-shock results can be significantly altered as a consequence of large-scale, meandering magnetic lines of force. Because the perpendicular diffusion coefficient κ ⊥ is generally much smaller than the parallel diffusion coefficient κ , energetic charged particles are trapped and preferentially accelerated along the shock front in regions where the connection points of magnetic field lines intersecting the shock surface converge, and thus create "hot spots" of accelerated particles (see also Kong et al, 2017;Kong et al, 2019a). For regions where the connection points are separated from each other, the acceleration to high energies will be suppressed.…”
Section: Implications To Variability Of Energetic Particlesmentioning
confidence: 99%